Environmental Sustainability in the Public Services Company of Sogamoso S.A. ESP. In the period 2013-2014 - Báez Mancera, Luis Germán (Scientia et Technica, 2018)
The contamination of rivers, lagoons, dams and other wastewater bodies has become a major concern due to its impact on the quality of life of the population and the development of economic activities that require the use of water of such bodies. This concern has led to the emergence of an administrative legal framework for regulating this problem, which, in turn, has stimulated the growth of investments in environmental sanitation projects. Considering that the use of these resources means a high opportunity cost, it is very important to raise the quality of such investments through the improvement of their social profitability